Hierarchy of Expressive Culture in Birdman - Dhania Putri Sarahtika; Nur Saktiningrum (Lexicon, 2018)
Despite the accolades that it has received, Birdman or (The Unexpected Virtue of Ignorance) has not been thoroughly studied in the academic sphere. This research attempts to examine the hierarchy of expressive culture portrayed in the screenplay of Birdman using Lawrence W. Levine’s theory (1988) of cultural hierarchy. A sociological approach by Swingewood & Laurenson (1972) is applied to see the work’s relation to the society. Firstly there is highbrow/lowbrow categorization, followed by an analysis of the challenges to the hierarchy; each process includes comparison between the findings and the reality in the present-day American society to see their resemblance.